2022
DOI: 10.1007/s10787-022-01098-5
|View full text |Cite
|
Sign up to set email alerts
|

Maltol ameliorates intervertebral disc degeneration through inhibiting PI3K/AKT/NF-κB pathway and regulating NLRP3 inflammasome-mediated pyroptosis

Abstract: Objectives As one of the major causes of low back pain, intervertebral disc degeneration (IDD) has caused a huge problem for humans. Increasing evidence indicates that NLRP3 inflammasome-mediated pyroptosis of NP cells displays an important role in the progression of IDD. Maltol (MA) is a flavoring agent extracted from red ginseng. Due to its anti-inflammatory and antioxidant effects, MA has been widely considered by researchers. Therefore, we hypothesized that MA may be a potential IVD protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Previous studies have found that the mitogen‐activated protein kinase (MAPK), nuclear factor‐kappaB (NF‐κB), and PI3K/AKT/mTOR signaling pathways play a crucial role in the progression of IVDD. 20 , 38 , 39 , 40 Therefore, these three signaling pathways were studied to further explore the mechanisms of API against IVDD. P‐P38, P‐ERK, P‐JNK, and P‐P65 were significantly upregulated following IL‐1β stimulation (Figure 5A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that the mitogen‐activated protein kinase (MAPK), nuclear factor‐kappaB (NF‐κB), and PI3K/AKT/mTOR signaling pathways play a crucial role in the progression of IVDD. 20 , 38 , 39 , 40 Therefore, these three signaling pathways were studied to further explore the mechanisms of API against IVDD. P‐P38, P‐ERK, P‐JNK, and P‐P65 were significantly upregulated following IL‐1β stimulation (Figure 5A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…NLRP3/Caspase-1 axis activation plays an important role in neuroinflammation and neuronal injury in various neurological diseases. 52,53 Previous studies have identified the effect of pyroptosis in nucleus pulposus cells during IDD, 14,54,55 and recently, Caspase-1 and NLRP3 expression has been reported to be upregulated in CEP of patients with degenerative disease. 56 Consistently, as both in vivo and in vitro studies presented in the current study, Au inhibited the phosphorylation of P65 and reduced the activity of NF-κB signaling, thereby decreased the expression of NLRP3 and Caspase-1, suggested that Au reduced chondrocyte pyroptosis by decreasing the activation of NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Highly active NF-κB signaling contributes to programmed chondrocyte death such as apoptosis and pyroptosis, which exacerbates CEP calcification. 14 , 15 The NLR pyrin domain containing 3 (NLRP3) inflammasome is a multiprotein complex composed of NLRP3 and the inflammatory protease Caspase-1, in addition, hyperactivation of NLRP3 inflammasome implicated in a wide of inflammatory disorders. 16 , 17 Besides, the NLRP3 is downstream of the NF-κB signaling pathway, and activation of the NLRP3 inflammasome leads to IDD by promoting pyroptosis in NP cell, and ECM degradation in IVD.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al showed that maltol, as a flavoring agent extracted from red ginseng, slowed IVDD development through the PI3K/AKT/NF-κB signaling pathway and NLRP3 inflammasome–mediated pyroptosis, which may be a viable medication for IVDD treatment (Gong et al . 2023 ). As an effective component of traditional Chinese medicine, ginsenoside Rg1 had been proved to promote ECM synthesis and cell proliferation, and inhibit apoptosis in degenerative NP cells via inhibiting the Wnt/β-catenin pathway, to alleviate the IVDD progress in the previous study (Yu et al .…”
Section: Discussionmentioning
confidence: 99%